Mechanically Exfoliated Multilayer Graphene-Supported Ni-MOF Parallelogram Nanosheets for Enhanced Supercapacitor Performance - Zhiheng Li; Junming Xu; Xinqi Ding; Haoran Zhu; Jianfeng Wu (Nanomaterials)
Metal–organic frameworks (MOFs) are regarded as advanced supercapacitor materials owing to their high surface area, redox-active sites, and porosity. However, their insufficient charge carrier mobility remains a critical limitation for practical application. Integrating MOFs with conductive carbon substrates is an effective strategy to break through this limitation. However, conventional carbon materials often require complex preparation methods and pre-activation steps for use in MOF composites. Herein, multilayer graphene (MLG) mechanically exfoliated from expandable graphite is employed as a substrate, and a van der Waals force-assisted chemical deposition method is developed to directly anchor Ni-MOF onto its surface without requiring pre-activation treatment. To optimize the composite, Ni-MOFs with various mass loadings are synthesized on MLG surface. The morphological characteristics and energy storage performance of these composites are thoroughly characterized. Ni-MOF/MLG-0.30 (with a 70.8% Ni-MOF loading on MLG) features a porous stacking structure of well-crystalline Ni-MOF parallelogram nanosheets on MLG, exhibiting optimal electrochemical performance. The composite achieves 1071.4 F·g−1 at 1 A·g−1, and a capacitance retention of 64.9% at the elevated current density of 10 A·g−1. Meanwhile, the composite maintains 63.2% of its initial capacitance after 5000 charge/discharge cycles at 4 A·g−1. A hybrid supercapacitor is fabricated using Ni-MOF/MLG-0.30 cathode and activated carbon anode, delivering 27.9 Wh·kg−1 energy density at 102.5 W·kg−1 power output.